Fibrin D-Dimer, Haemostatic Factors and Peripheral Arterial Disease - Lee, Amanda J; Fowkes, F Gerald R; Lowe, Gordon D O; Rumley, Ann (Thrombosis and Haemostasis, 1995)
Several haemostatic factors have been shown to have a predictive role in cardiovascular disease, although their relationship with prevalent peripheral arterial disease is not well reported. Using a random sample of 1592 men and women aged 55-74 years from Edinburgh, Scotland, we examined the relationship of von Willebrand factor (vWF), tissue plasminogen activator (t-PA) and fibrin D-dimer antigens and factor VII activity to peripheral arterial disease. t-PA antigen and fibrin D-dimer showed significant linear trends of increased levels with increasing severity of disease in both sexes (p ≤0.01) and vWF showed a similar pattern in men only (p ≤0.01). On multivariate analysis, fibrin D-dimer was independently related to the risk of intermittent claudication (p ≤0.01) and, among men, to the extent of arterial narrowing in the lower limb, as measured by the ankle brachial pressure index, (ABPI) (p ≤0.001). These results are further evidence of a role for intravascular fibrin deposition in the development of peripheral atherosclerosis.